A Critique of the Assessment of Professional Skills - Anne Hewitt (Legal Education Review)
[Extract] It is perhaps a conceit of law teachers to think that their area of law poses special challenges for educative purposes. In this paper, I suggest that administrative law does present some particular problems for students, although I am sure that the issues are not completely unique to this legal fi eld. In any case, my experiences over some years have led me to explore some educational theory and practice that may be of broader interest to law teachers, and not only those involved with administrative law